Upcycling plastic waste into syngas: development of gasification slag supported NI catalysts for steam reforming of pyrolysis gas - Ong, Hang Meng (Nanyang Technological University, 2022)
Upcycling pyrolysis gas from plastics (70 wt% PP, 6 wt% LDPE, and 24 wt% HDPE) was explored using slag supported Ni catalysts without promoters and promoted with Cr, Mo and W (Ni, Ni-Cr, Ni-Mo, and Ni-W). The objective is to understand the promoting effects of Cr, Mo and W on gasification slag supported Ni catalysts during steam reforming of mixed hydrocarbon compounds. The catalytic activity and coke resistance of the promoted Ni catalysts were investigated for efficient upgrading of plastic pyrolysis gas to syngas. The reforming experiments were conducted at 800 °C for 3 h with steam-to-carbon molar ratio of 7. Catalyst characteristics were studied using BET method, TPR, XRD, SEM, CHNS elemental analysis, and TGA. Gas composition after steam reforming was determined using gas chromatography. Ni-Mo catalyst had the highest hydrocarbon conversion, hydrogen yield, and was less prone to coking. The superior catalytic activity observed from the Ni-Mo catalyst could be attributed to the formation of Ni2Mo3O8 phase, which led to dispersion and stabilization of active Ni species in the form of metal alloy upon reduction. The formation of the reducible species on slag supported catalyst suggest its potential for valorization. The formation of CaMoO4 in Ni-Mo and CaWO4 in Ni- W could be attributed to the solid reaction of the Mo and W promoters with the slag during calcination. Different degree coke deposition was observed over the catalysts, due to the difference in catalytic activity.